A Patient With Insulinoma in Nesidioblastosis: Anesthesia Practice in Angiography (Case report) - Arslan, Mustafa; Öztürk, Levent; Güngör, İrfan; Ünal, Yusuf; Çekmen, Nedim; Alkan, Metin (Fırat University, 2005)
Insulinoma, characterized by hyperinsulinism, is a functional tumor of the pancreas. Nesidioblastosis is determined by hyperplasia in the pancreatic cells and hyperinsulinemic hypoglycemia, although it is encountered predominantly in the neonatal period, it can also be observed in the adults. A seven years old boy weight 24 kg with hyperinsulinemic hypo glycemic infantl spasm was clinically followed up. His blood glucose level was 26 mg/dL when he first applied to the hospital. He was given 2 mg/kg (48 mg) propofol general anesthetic and 0.5 mg/kg atracurium with endotracheal intubation. His periferial O2 saturation, noninvasive blood pressure and pulse rate was followed throughout angiography. Anethesia propofol was given as 2 mg/kg/hour with remifentanil 0.1 µg/kg/min infusion. Blood glucose level was tested every 15 min during angiography, glucose level was 65-69 mg/dL, blood O2 saturation was between 97-99 % blood pressure 90-100/50-60 mmHg and pulse rate between 78-84/min. Our case was given anesthesic for 75 minutes, propofol and remifentanyl infusion was stoped after that the patient was extubated without any problems. In this case, we performed general anesthesia by using propofol and remifentanil infusion during angiography. In our study, we observed that propofol and remifentanil infusion to be useful maintained the hemodynamic stability and had no adverse effect on the blood glucose level. As a result in patients with insulinoma; attention should be taken to anesthetic agents for their effects on hemodynamic conditions and blood glucose levels. We decided that the anesthesia spesialist could be confronted with sudden changes in preoperative blood glucose levels, because of that reason close blood glucose level following is very important in these type of patients.©2005, Fırat Üniversitesi, Tıp Fakültesi

Insülinoma; pankreasın, hiperinsülinizmle giden fonksiyonel tümörüdür. Nesidiobilastozis: pankreas hücrelerinde hiperplazi ve hiperinsülinemik hipoglisemi ile tespit edilen, neonatal dönemde dominant olarak görülmekle beraber yetişkinlerde de görülebilmektedir. Yedi yaşında, 24 kg ağırlığında hiperinsülinemik hipoglisemik, infantil spazm tanısı ile izlenen erkek hasta. Hastaneye ilk başvurusunda plazma glukoz konsantrasyonu 26 mg/dL idi. Açlık süresi boyunca hastaya 2.5 mL/kg/saatte gidecek şekilde % 5'lik dekstroz infüzyonu yapıldı. Anesteziye 2 mg/kg (48 mg) propofol ile başlandı, 0.5 mg/kg atrakuryum ile trakeal entübasyon uygulandı. Anjiografi süresince hasta; periferiyel O2 satürasyonu, noninvaziv kan basıncı, nabız sayısı yönünden sürekli izlendi. Anesteziye propofol 2 mg/kg/saat ve remifentanil 0.1 µg/kg/dk infüzyonu ile devam edildi. Hastanın kan glukoz düzeyi 15'er dk'lık aralarla tüm anjiografi süresince bakıldı ve glukoz konsantrasyonu 65-69 mg/dL, O2 satürasyonu %97-99, kan basıncı 90-100/50- 60 mmHg ve nabız 78-84 atım/dk arasında ölçüldü. Hastaya 75 dk süre ile anestezi verilerek, anjiografi bitiminden sonra propofol ve remifentanil infüzyonu sonlandırıldı. Hasta herhangi bir problem olmadan ekstübe edildi. Sonuç olarak insülinomalı hastalarda hemodinamiyi ve kan glukoz düzeyini etkilediği için kullanılacak anestezik ajanlara dikkat edilmeli ve peroperatif kan glukoz düzeyinin ani değişiklikleri ile karşılaşılabileceği düşünülerek yakın kan glukoz düzeyi takibinin önemli olduğu kanısına vardık. ©2005, Fırat Üniversitesi, Tıp Fakültesi
İnsülinomalı Bir Nesidioblastosis Olgusu: Anjiografide Anestezi Uygulaması